Responsible consumerism - Mhd. Sarif, Suhaimi; Ismail, Yusof; Zainudin, Dolhadi (Sejahtera Consumerism, Department of Business Administration, KENMS, IIUM, 2023)
This textbook provides students with exposure to consumerism with sustainable development. Sustainable development integrates all aspects of consumerism, applicable to both consumers and producers. Students will gain exposure on consumerism topics that include consumption, market players’ behaviours, consumer protection and tights, institutions, and systems of consumer protection. Moreover, this textbook incorporates Sustainable Development Goal (SDG) 12, that is to achieve prosperity, peace, and unity in the world through responsible consumption and production. This text is prepared for the course entitled Responsible Consumerism, and becomes part of a project at the Kulliyyah (Faculty) level. The Kulliyyah is related to multiple stakeholders that include International Islamic University Malaysia (the Host of RCE Greater Gombak), the internal Kulliyah community, and Consumer Association of Penang (CAP). CAP serves as a network partner of IIUM and RCE Greater Gombak in consumerism advocacy and a training provider for consumerism. The textbook project also incorporates the Falsafah Pendidikan Kebangsaan (PFK) or National Education Philosophy Malaysia, to create and sustain a peaceful, unity and prosperous world, and is known as Sejahtera According to Kamus Dewab Bahasa (DBP), Sejahtera is a Malay word which means aman (peace), makmur (prosperity), tenang (tranquility), senang (ease) and terpelihara daripada bencana kesusahan (free from any hazardous incidents). It can be translated as a condition or position where it is prospered and free from any hazardous activities or consequences whether right now or in the future. ] World. Sejahtera has a strong influence in Malaysia, particularly, consumerism. The textbook discusses the responsible consumerism that has been promoted by the United Nation Development Program (UNDP), specifically its 12th SDG Goal: Responsible Consumption and Production. Apart from that, the topic also reinforces the spirit of the National Education Philosophy (Falsafah Pendidikan Negara) that upholds a balanced development between Intellectual, Spiritual, Emotion and Physical (ISEP) aspects of human existence. With a strong support by International Islamic University Malaysia (IIUM) as a pioneer Islamic university in Malaysia that aims to imbue the Islamic values with the modern practice of knowledge, it welcomes the SDG goals promoted by UNDP.